Letter from the Editors - Xavier, José Roberto Franco; Silva, Paulo Eduardo Alves (Revista de Estudos Empíricos em Direito, 2014)
It is with immense satisfaction that we present the first issue of the Brazilian Journal of Empirical Legal Studies. An initiative of the Brazilian Network of Empirical Legal Research, the aim of the periodical is to fill a gap in the law publication area in Brazil. This is due to the fact that there currently is no other journal that specifically focuses on empirical research in law.